Generalized Riemann problems in computational fluid dynamics - Ben-Artzi, Matania, 1948- (Cambridge monographs on applied and computational mathematics ;, 2003)
The Generalized Riemann Problem (GRP) algorithm comprises common schemes of numerical simulation of compressible, inviscid time-dependent flow. This monograph, including examples illustrating the algorithm's applications, presents the GRP methodology beginning with its underlying mathematical principles. The book is accessible to researchers and graduate students of applied mathematics, science and engineering.